The physic-chemical assessment of urban river basin using macroinvertebrate indices for the environmental monitoring of urban streams - O, Gotore; A. Munodawafa; R. Rameshprabu 3; T.P. Masere; V. Mushayi; T. Itayama (Tehran Urban Research and Planning Publication Center, 2022)
: The major sources of pollution along the Mukuvisi River are industrial effluents from Msasa, Graniteside, and Southerton industrial sites, sewage effluent from Firle sewage works, pesticide and fertilizer runoff from Pension and surrounding farms, and domestic and diffuse pollution from residential areas. The primary objective of this study was to assess the impact of point and non-point pollution sources on macroinvertebrates variability and investigate the seasonal water quality deterioration along the Mukuvisi River. To evaluate macroinvertebrate community diversity using South African Scoring System 5 protocol for rapid bioassessment of water quality. The combined application of benthic macroinvertebrates and physic-chemical parameters was the focus of this research to validate the water quality status of the urban River systems concerning emerging pollutants in urban areas.